Legal Liability for Use of Electric Mouse Traps Causing Death - Isnaini, Enik; Royani, Ahmad; Manggala Putera, M. Yuda (Jurnal Independent, 2024)
ABSTRACT In criminal law, offenses are divided into two, namely culpa (negligence) and dolus (intentional) offenses. The number of cases of death resulting from the installation of electrified rat traps that have occurred recently is due to the farmers' lack of awareness of the risks that can occur. This is a criminal act of negligence, in which the perpetrator causes the loss of life of another person. The provisions regarding the criminal offense of negligence that causes death are regulated in Article 359 of the Criminal Code. The installation of electric current that results in the loss of life of another person can be classified as a criminal act of negligence, where due to negligence the perpetrator electrified his rice field fence with high-voltage electric current resulting in the death of a person. Based on this background, the author proposes the formulation of the problem, namely the first is how the regulation of criminal acts of negligence according to the Criminal Code ?. And the second is how the legal sanctions against the perpetrators of the use of electrified rat traps that cause the victim to die ?. This research method uses normative juridical research type, with statutory approach (statue approach) and concept approach (concep) of law. From the results of the study it can be concluded that the Pengalturaln tindalk pidalnal keallpalaln according to the Criminal Code is dialtur dallalm palsall 359 Dimalnal dalpalt dipidalnalnyal oralng yalalebalbkaln maltinyal oralng lalin kalrenal kesallalhalnyal altalu keallpalalnyal. The legal sanction against the perpetrators of the use of electric rat traps is set forth in Article 50 paragraph (1) of Law No. 30 of 2009 Concerning Electricity is punishable by a maximum imprisonment of 10 (ten) years and a maximum fine of Rp.500,000,000.00 (five hundred million rupials). The falsification of electric current which results in the downtime of traffic in the dalpalt is classified as one of the acts of pidalnal negligence. The punishment for the use of electric rat traps that caused the death of a jugal victim has been regulated in several articles of Article 359 of the Criminal Code with a penalty of imprisonment of at least one year and a penalty of imprisonment of at least one year. Thus it is hoped that the importance of awareness of the applicable legal regulations in order to create a safe and peaceful environment which is the goal of the law itself.